Tyrosine kinase inhibitors rechallenge in solid tumors: a review of literature and a case description with lenvatinib in thyroid cancer. Issue 12 (2nd December 2017) - Felicetti, Francesco; Nervo, Alice; Piovesan, Alessandro; Berardelli, Rita; Marchisio, Filippo; Gallo, Marco; Arvat, Emanuela
ABSTRACT: Introduction : In the last decade tyrosine kinase inhibitors (TKIs) have been employed for a wide range of hematological and solid tumors and today they represent a valid therapeutic option for different neoplasms. Among them, both sorafenib and lenvatinib were approved for the treatment of radioactive iodine (RAI) refractory differentiated thyroid carcinoma (DTC). Unfortunately, in some cases the efficacy of TKIs is limited by the onset of drug resistance after the initial response. Areas covered : We report the case of a patient with a RAI refractory advanced DTC, treated with lenvatinib after surgery, multiple RAI administrations, traditional chemotherapy, and sorafenib. During treatment with lenvatinib, a noticeable response was detected by sequential computed tomography scans but, after 27 months, tumor progression became evident and led to lenvatinib interruption. In absence of any active treatment, a further disease progression was documented, and lenvatinib was re-administered obtaining a new objective response. Starting from this case report, we review available reports about the rechallenge with TKIs in solid tumors, discussing the possible mechanisms underlying the efficacy of this approach. Expert commentary : Rechallenge with TKIs in solid tumors could be a therapeutic option in subjects with advanced and metastatic DTC who experience a progressive disease after initial response to lenvatinib.